Participation of local entities in the water management of the Piracicaba, Capivari e Jundiaí - Sugahara, Cibele Roberta; Lourenco, Bianca Maria; Silva, Luiz Henrique Vieira da; Ferreira, Denise Helena Lombardo; Mariosa, Duarcides Ferreira (Technical and Scientific Journal Green Cities, 2025)
The adoption of measures and procedures for local participation in water management, as well as the planning of water resources according to the use of different sectors are foreseen in the Sustainable Development Objective 6 of Agenda 2030. This study seeks to point out the local participation in water management, in order to highlight the importance of the local community in the management of water resources. As a methodology, bibliographic research is adopted with a qualitative approach and documentary technical procedure. As evidenced in the study, the importance of local participation in water management is recognized mainly in the management of hydrographic basins. It is argued that this is how organizations, and the local community can collaborate with decision-making for water resource management, observing the issues involved in studies on water allocation, reuse of water resources and systems for real-time monitoring. and guarantee of supply of water resources, as defended, for example, by CBH-PCJ. The participation of society in the management and monitoring of water should be considered as a way of expanding the discussions and potential adjustments of the water service situation for the population of the municipalities involved in the hydrographic basins. It is believed that the involvement of society in water management makes it possible to create initiatives to prevent water crises and interventions for the rationing of water use in line with the actions provided for in river basin plans.
Keywords: Hydrographic Basins; Hydrographic Basin Committees; Water Management